Health Consumer Expectations and Perception of Quality Care Services at Primary Health Care Level in Nigeria - Jimoh, Saka Mohammed; Mankanjuola, Akande Tanimola; Oluwatoyin, Saka Aishat; Fatai A, Bello; Babaita, Isiaka Sulu (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: The study examined the expectations of health consumers and perception used in judging the Quality of health care services at the primary health care level. METHODOLOGY: A cross-sectional study was carried out among randomly selected health consumers that had received health care services in the hospitals designated as primary health care facilities in Kwara State Nigeria. RESULTS: Overall health consumers’ means score expectations was 6.57 while perception was 5.80. Though was high in favour of females with no statistics significant difference. However, correlation test revealed significant association in socio-demographic variables such as age, occupation and educational status. Conversely, relationship was inverse in term of increase in education attainment with lower perception value (pv = <0.001). CONCLUSIONS: Expectation- perception gap was a major determinant of quality of health care services at primary health care levels. Significant relationship occurred between heath consumer’s age, occupation, educational status and overall expectation -perception of quality health care received. It is recommended that hospital management need to monitor the link between the expectations including perception of services received by patients for quality improvement at primary health care level.